Expression of TCRγδ receptor genes in jejunum mucosa of baby alpacas (Vicugna pacos) - Mendizábal J, Simón (2017)
The aim of this study was to determine the expression of TCRγδ receptor genes (gamma and delta) in the jejunal epithelium of 16 apparently healthy baby alpacas (2 to 47 days of age), by quantifying messenger RNA (mRNA) using specific primers. Jejunumsamples (2 cm long) were collected. Total mRNA of the medium portion of the jejunum acted as template for complementary DNA synthesis by reverse transcription (RT), followed by real-time PCR for the amplification and quantification of the mRNAs of the polypeptides that make up the gamma and delta chains of the TCR. The 2-ΔΔCt method was used for the relative mRNA quantification, using as calibrator two neonatal alpacas that had not consumed colostrum. The alpacas of 1, 2, 3 and >4 weeks of age expressed the gamma gene at 4.75, 6.78, 16.24 and 103.11 folds as expressed by the calibrator animals, respectively, and the delta gene was expressed at 9.43, 20.78, 25.08, and 146.46 folds, respectively. The results demonstrate that gamma and delta genes are increasingly expressed with age, and significantly from the fourth week of age (p<0.05), indicating that Tγδ lymphocytes increase in the intestinal mucosa with age.